Internal Communication - Rathouský, Tomáš; Quigley, Martin John David; Mýtná, Dominika; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2015)
The diploma thesis focuses on characteristics of internal communication, its implementation in various forms in different companies and analysis of the internal communication in one selected company. After the analysis of its current state in the multinational company, the thesis will recommend improvements to the areas of internal communication and human resources, with the main focus of global implementation of these recommendations.
Vedoucí práce: Martin John David Quigley
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses